Zakat as a measure of social justice in Islamic Finance : an accountant’s overview / Pranam Dhar. - Dhar, Pranam (Universiti Teknologi Mara Selangor, 2013)
Zakat is an important form of religiously mandated charity under Islam. It is the third pillar of Islam. The giving of Zakat is important for Muslims, as this leads to purification of their wealth from all sins. This paper examines the role of Zakat as an instrument of social justice and poverty eradication in society. Each Muslim calculates his or her own Zakat individually. Generally, this involves the payment each year of two and a half percent of one's capital, after the needs of the family have been met. One can donate additional amount as an act of voluntary charity but Zakat is fundamental to every Muslim. Zakat is the Islamic contribution to social justice: those who have to give charity share the benefit of their prosperity to those who have fallen short. This is the Islamic approach to remove greed and envy and to purify one's soul based on good intentions. This is the institution of Zakat in Islam. The institution of Zakat serves to eradicate poverty in the community and uphold the light of Islam. Allah says “whatever is paid as Zakat for the sake of Allah shall be rewarded in manifolds”.